(untitled) (Atlanta, Ga., 1995)
Clinical Oncology, the American Cancer Society''s textbook of cancer, presents a wealth of information about the wide range of issues in cancer. This exciting new resource will help healthcare providers adopt practices to encourage prevention and early detection, as well as provide state-of-the-art diagnosis and treatment.
Keywords: Cancer,Oncology,Ung thư học